Enhancing Transaction Cost Efficiency and Customer Acquisition Through E-Invoicing and E-Payment Systems - Dwi Saraswati; Joana Lindawati Saragih; Iskandar Muda (Yayasan Multidimensi Kreatif, 2026)
This research is a study that explains the differences that occur in an e-invoice and e-payment spending cycle on saving transaction costs and increasing the number of customers in the manufacturing industry. These changes occur very significantly and have a huge impact on the development of accounting information systems. The purpose of this study is to see whether E- Invoicing and E-Payment in the implementation of the expenditure cycle minimize transaction costs and increase the number of customers in the manufacturing industry. The research method used in this research is descriptive method, in which the researcher only conducts a literature study and then develops it into a paper. The results of this study explain that e-invoicing and e-payment have a very positive impact in minimizing the accounting costs incurred by the expense cycle. The expense cycle does not require many human resources when using an electronic system. The use of e-invoicing technology in manufacturing operations can significantly reduce production costs and increase efficiency. E-invoicing and e-payment are a must to adapt to the digital business model in the era of industrial revolution 4.0.